Financial framework of higher education in Malaysia - Ujang, Zaini (Penerbit UTM, 2013)
Rarely do authors discuss in detail issues related to the financial framework of higher education. In the context of Malaysia,the country’s leadership has put in place mechanisms to transform higher education. Commencing 2004, the government has transformed higher education through the establishment of the Ministry of Higher Education. Accordingly, the National Higher Education Strategic Plan was drafted to elevate the status and prestige of local universities internationally.